Design Considerations for Conducting Large‐Scale Learning Research Using Innovative Technologies in Schools. Issue 1 (11th December 2018) - Uncapher, Melina R.
ABSTRACT: Since the advent of computers, scientists who study how people learn have been utilizing technology to uncover the cognitive and neural mechanisms of learning. Recent technological advances have allowed learning scientists to move their research out of the lab and into the wild, to investigate how students learn in real‐world environments. However, the move from the lab to the classroom involves a significant shift in strategy, requiring consideration of factors varying from the design of mobile (vs. lab‐based) technology to the recruitment of participants, as well as the contextual variables to account for in the less‐controlled environment of schools. Here I discuss the learnings our group has gleaned from a research program involving over a thousand elementary and middle school students in a longitudinal, multi‐year design that involves technologies for assessment and improving learning in schools.